Strategic planning. Level of use of strategic planning tools in companies in Nova Serrana (Research, Society and Development, 2023)
Strategic planning tools are used by industries to enhance and develop the knowledge needed to build goals, helping companies achieve better results. This study analyzes the awareness and use of these tools by entrepreneurs in the footwear industries of Nova Serrana. To respond to the research problem, a questionnaire was applied to 250 (two hundred and fifty) people, with only 73 (seventy-three) answers, and the results show that entrepreneurs know little about strategic planning tools, and most of them see these tools as an expense and not as an investment. Thus, it is highlighted how strategic planning tools are of great importance for companies to have a broad, safe, and efficient vision of the future, correcting errors with goals and proper planning, and obtaining the necessary information for decision-making, placing them in a good position in the market.